Cardioprotective effect of NRG-4 gene expression on spontaneous hypertension rats and its mechanism through mediating the activation of ErbB signaling pathway - Yang, Zhang; Yaling, Wang; Tao, Liu; Mingyue, Rao; Yongjun, Li (Cellular and Molecular Biology, 2022)
To explore the myocardial protective effect of Neuregulin-4 (NRG-4) gene expression on spontaneous hypertension (SHR) rats and its mechanism through mediating the activation of the ErbB signaling pathway, this study was conducted. For this purpose, forty 24-week-old male SPF SHR rats were selected as the experimental group, and 10 age and sex-matched Wistar Kyoto (WKY) rats were selected as the control group. Cardiac tissues were collected for hematoxylin-eosin (HE) staining, terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) staining, Masson staining, and immunohistochemical staining. Following tail vein injection of recombinant lentiviral vectors, the experimental groups were constructed as the control group (SHR rats without any treatment), Empty vector group (Empty Vector transfection), shRNA negative control (NC) group (LV-shRNA-NRG-4 NC transfection to silence the expression of NRG-4), shRNA group (LV-shRNA-NRG-4 transfection), pcDNA3.1(-) NC group (pcDNA3.1(-)-NRG-4 empty vector transfection) and pcDNA3.1(-) group (pcDNA3.1(-)-NRG-4 transfection to overexpress NRG-4). Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot were used to detect the expression levels In addition, methyl thiazolyl tetrazolium salt (MTT) assay and flow cytometry were performed to detect the proliferation and apoptosis of cardiomyocytes, respectively. Results showed that in the SHR group, the cardiomyocytes showed hypertrophy, disordered arrangement, hyperchromatic nucleus, irregular shape, obvious rupture of myocardial fibers, and obvious proliferation of fibrous stroma; obvious myocardial fibrosis, and there were more blue collagen fibers around cardiomyocytes and myocardial arterioles; cardiomyocytes were swollen, muscle fibers arranged disorderly, collagen around the coronary artery and myocardial interstitium increased significantly with a cross-linking appearance; besides, compared with WKY group, the apoptosis index of cardiomyocytes in SHR group was significantly increased (P<0.05). The expression of NRG-4 protein was decreased in the SHR group compared with the WKY group (P<0.05). In vitro, there was no difference in the mRNA expression of NRG-4, ErbB2 and ErbB4, MMP2, TGFβ1 and α-SMA, as well as Caspase3, Bax and Bcl-2 among the control group, Empty vector group, shRNA NC group and pcDNA3.1(-) NC group (P>0.05). While shRNA group showed decreased expressions of NRG-4, ErbB2, ErbB4, MMP2, TGFβ1, α-SMA and Bcl-2, while increased Caspase3 and Bax expressions, as well as promoted cell proliferation and cell apoptosis when compared with the shRNA NC group (P<0.05); while compared with pcDNA3.1(-) NC group, pcDNA3.1(-) group had highly increased expressions of NRG-4, ErbB2, ErbB4, MMP2, TGFβ1, α-SMA and Bcl-2, while decreased Caspase3 and Bax expressions, inhibited cell proliferation and cell apoptosis (all P<0.05). It is concluded Upregulation of NRG-4 gene expression can promote the activation of the ErbB signaling pathway, thus inhibiting the proliferation and apoptosis of cardiomyocytes in SHR rats, reversing myocardial fibrosis, and playing its cardioprotective role.